A study on infant feeding practices in the urban slums: a cross sectional study - D., Rajesh; D., Bhavana (International Journal of Contemporary Pediatrics, 2016)
Background: Infant feeding practices comprising of both breastfeeding (BF) as well as complementary feeding (CF) have major role in determining the nutritional status of the child. Infant and young child nutrition is extremely important as it not only lays the foundation for good health throughout the life but, also provides a good workforce. Methods: The purpose of the study was to assess the current infant feeding practices in children between the age group of 6months-1years, to find the reason for inappropriate CF practices and to assess the knowledge of mothers regarding CF. Results: Out of 150 children studied, 33 (22%) had practiced exclusive breast feeding, and 91 (60.7%) children received CF at the appropriate time i.e., around 6 months, 87 (58%) gave complementary feeds with appropriate consistency, 49 (32%) gave with appropriate frequency and 98 (65.5%) with appropriate amount so overall prevalence of the optimal complementary feeding was only 28 (18.7%). Conclusions: There is an urgent need to bridge the “knowledge gap” and “practice gap” of mother’s from urban slum and lower socio economic strata of the community by further strengthening the on- going breastfeeding programme, breastfeeding knowledge and practice of mothers in urban slum areas.